Simultaneously realizing intelligent color change and high haze of κ-carrageenan film by incorporating black corn seed powder for visually monitoring pork freshness. (15th February 2023) - Chi, Wenrui; Liu, Wenhua; Li, Jian; Wang, Lijuan
Graphical abstract: Highlights: All-black corn seed powder/κ-carrageenan films were prepared. The composite films exhibit simultaneous pH-sensitivity and high-haze. The 50BC50κC can effectively monitor the freshness of protein-rich foods. Abstract: Although intelligent films containing various anthocyanins have exhibited a good pH-response, high light-transmittance makes it difficult to accurately observe color changes in monitoring food freshness. In this study, black corn seed powder (BCSP) containing anthocyanins, starch, lipid and fibers, was used to provide κ-carrageenan film (κCF) with simultaneous intelligent color change and high haze. As the mass ratio of BCSP to κ-carrageenan increased from 1:4 to 1:1, the haze of composite films increased from 49.44 % to 79.25 %, the transmittance decreased from 43.62 % to 18.90 %, respectively. The composite films turned from red to green along with the increase of pH from 2 to 10. When the TVB-N of pork increased from 2.7 ± 0.15 mg/100 g to 14.03 ± 0.14 mg/100 g, the 50BC50κC changed from pink to greyish-green and the haze increased up to 91.83 %, which will make it more visible and effective to indicate food freshness and popular for use.